Literature Review: The Effectiveness of the Teams Games Tournament (TGT) Learning Model for Chemistry Subjects on Student Learning Outcomes. - Puspareni, Chyndi Nadhea; Romadhoni, Intan Kurnia; Rahmawan, Setia (Universitas Lampung, 2024)
Abstract : Since chemistry is one of the more difficult topics, student success in the subject is often poor. Using the cooperative learning model Teams Games Tournament, which combines games and academic competitions to maximize classroom engagement, is one way to enhance student learning results. The goals are to evaluate the benefits of the TGT model in creating student learning outcomes and to investigate the TGT learning model's effectiveness in enhancing learning outcomes. Method: review of the literature. In summary: Numerous inferences may be made in light of the findings of the literature review research, including: (1) There is hope that the Teams Games Tournament (TGT) concept can significantly improve studentKeywords: Cooperative Learning, Teams Games Tournaments, Chemistry. DOI: 10.23960/jppk.v13i2.29849